Reading habits among year 6 pupils on the reading of english reading materials: a study in Sekolah Kebangsaan Empila Samarahan, Sarawak / Jeffery Hj. Zen - Hj. Zen, Jeffery (2004)
The purpose of this study being conducted was to investigate on the factors that influenced the reading habits among the Year 6 pupils of S.K Empila, Samarahan for the year 2004 in the reading of the English reading materials. The process of data extracting for the research involved a questionnaire survey On the respondents of equal in numbers comprising of 18 boys and 18 girls. In addition to that, some interviews and observations were done at random. Responses and findings were analyzed in descriptive analysis and using SPPS program.